Perancangan Mesin Virtual Reality (VR) Sterilizer Kelapa Sawit Sebagai Media Pembelajaran Teknologi Pengolahan Kelapa Sawit - Safwan; Feri Susilawati; Waniara (LPPM Politeknik Aceh Selatan, 2025)
This research aimed to make it easier for students and workers to understand how to work on a Sterilizer machine with hands-on practice in a virtual situation. This research used the multimedia development life cycle method. This MDLC method had 6 stages: concept, design, material collecting, assembly, testing, and distribution. Virtual Reality is built using Blender software, unity, and bridged by the C# programming language. Based on the results of research conducted on this research, the development of virtual Reality on this sterilizer machine makes it easy to understand how to work on it virtually without using the actual machine